2020
DOI: 10.1364/boe.403803
|View full text |Cite
|
Sign up to set email alerts
|

Bead-based multiplex detection of dengue biomarkers in a portable imaging device

Abstract: Dengue is one of the most rapidly spreading mosquito-borne viral diseases in the world. Differential diagnosis is a crucial step for the management of the disease and its epidemiology. Point-of-care testing of blood-borne dengue biomarkers provides an advantageous approach in many health care settings, and the ability to follow more than one biomarker at once could significantly improve the management of the disease. Bead-based multiplex technologies (suspension array) can measure multiple biomarker targets si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A broad area green LED illuminates the specimen plane using a set of aspheric lenses and an excitation filter (Fig. 2(a)) 64 . Experimental results demonstrated that the LED light source provides more uniform illumination across the specimen plane, and therefore permits the multiplex detection of three biomarkers.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…A broad area green LED illuminates the specimen plane using a set of aspheric lenses and an excitation filter (Fig. 2(a)) 64 . Experimental results demonstrated that the LED light source provides more uniform illumination across the specimen plane, and therefore permits the multiplex detection of three biomarkers.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Yuan et al [ 39 ] developed a portable imaging setup comprising microfluidic chips with an objective lens, prism, filters, and camera for the multiplex detection and quantification of a protein and human IgG related to dengue. Carboxyl-modified magnetic beads encoded with different concentrations of allophycocyanin dye provided unique spectral signatures.…”
Section: Spectroscopic Detectionmentioning
confidence: 99%
“…In many circumstances, however, clinical evaluation based on a single biomarker is not enough for adequate diagnostics and therapy monitoring. Multiplexing enables the simultaneous monitoring of multiple analytes and/or samples, which dramatically improves the possibility for diagnosis of many diseases, since detecting multiple biomarkers and their diagnostic correspondence in different biofluids [4] can give us more information about the disease, its status, and treatment [5,6]. Moreover, patients often suffer from several diseases simultaneously (for example, diabetes and gout) and thus, the simultaneous measurement of several biomarkers (glucose and uric acid) from a single drop of body fluid would dramatically reduce the pain and effort of the patients during self-management of their chronic diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This can be further extended by the separation into multiple channels [7,11], chambers [14], or wells [15]. Although these possibilities are mostly applied for electrochemical detection, using optical detection via labeling with differently colored dyes is an additional option for multiplexing [6,16]. For the realization of multiplexed biosensors, it is also possible to employ different biorecognition elements, including (monoclonal) antibodies, antigens, enzymes (such as glucose or lactate oxidase), or proteins [5,7,13,14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation